Specialized transducing phage lambda carrying the genes for coupling factor of oxidative phosphorylation of Escherichia coli: increased synthesis of coupling factor on induction of prophage lambda asn. - Kanazawa, H (1979)
Studies were made of the synthesis of the coupling factor complex (F1--F0) of oxidative phosphorylation after prophage induction of a set of Escherichia coli strains lysogenic for defective transducing phage lambda asn, lambda uncA, or lambda bglC. The transducing phages had been isolated from a strain of E. coli carrying prophage lambda cI857 S7 within the bglB gene located near the unc gene cluster [Miki, T., Hiraga, S., Nagata, T. & Yura, T. (1978) Proc. Natl. Acad. Sci. USA 75, 5099--5103]. When lysogenic cells carrying lambda asn and lambda cI857 S7 were induced at high temperature, synthesis of the F1-ATPase portion of the complex increased to severalfold that of the noninduced cells. In contrast, no increase was observed upon thermoinduction of cells carrying lambda uncA or lambda bglC. The number of membrane sites that could bind purified F1-ATPase also increased significantly upon induction by lambda asn but not by lambda uncA or lambda bglC. In addition, F1-depleted membranes prepared from lambda asn-induced bacteria required more dicyclohexylcarbodiimide to seal the proton pathway than did those from noninduced bacteria. These results strongly suggest that lambda asn carries a set of bacterial genes coding for all the F1 polypeptides (the alpha, beta, gamma, delta, and probably the epsilon subunits) and at least some of the genes involved in formation of F0 polypeptides. Although lambda uncA carries the structural gene (uncA) for the alpha subunit of F1-ATPase, it apparently does not carry the whole set of F1--F0 genes.